2021
DOI: 10.1590/s1980-220x2019023003679
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telephone monitoring on cancer patients undergoing esophagectomy and gastrectomy

Abstract: Objective: To evaluate telephone monitoring for symptoms, quality of life, distress, admissions to the emergency center and the satisfaction of cancer patients undergoing esophagectomy and gastrectomy. Method: Randomized controlled study in two groups, carried out at the Cancer Institute of the State of Sao Paulo; the intervention group received telephone monitoring for four moments after the surgery, while the control group received only institutional care. Results: Of the 81 patients evaluated, the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 15 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…Eleven of these studies showed no significant difference compared with traditional in-hospital specialist care, resulting in non-inferiority of the nurse- or general practitioner-led follow-up. Two studies 47 , 49 reported significant differences favouring the follow-up scheme conducted by specialist nurses, showing positive changes in HRQoL.…”
Section: Non-specialist Follow-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of these studies showed no significant difference compared with traditional in-hospital specialist care, resulting in non-inferiority of the nurse- or general practitioner-led follow-up. Two studies 47 , 49 reported significant differences favouring the follow-up scheme conducted by specialist nurses, showing positive changes in HRQoL.…”
Section: Non-specialist Follow-upmentioning
confidence: 99%
“…Three studies focused on a total of 565 patients after oncological gynaecological treatment; all were considered to have a low risk of bias. Sample size ranged from 24 to 385 37 , 47 , 49 . Two studies focused on nurse-led follow-up and one study considered patient-initiated follow-up as the minimal intensive follow-up.…”
Section: Gynaecological Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Post-operative telephone monitoring, following hospital discharge, of cancer patients, although already used, configured a highly effective alternative during the COVID-19 pandemic. This method allows continuity of care, providing education and guidance to patients according to their needs (4) . Another effective idea in surveillance actions is the early detection of cervical cancer (CC) through organized screening programs, which rely on Primary Health Care (PHC) to attract women for carrying out the cervix cytopathological examination, and then, if there is a high-grade squamous intraepithelial lesion, refer them to the secondary care network (5) .…”
Section: Introductionmentioning
confidence: 99%
“…O monitoramento telefônico de pós-operatórios, após alta hospitalar, de pacientes com câncer, ainda que já fosse utilizado, configurou uma alternativa altamente eficaz durante a pandemia da COVID-19. Esse método permite a continuidade do cuidado, oferecendo ensino e orientações aos pacientes de acordo com as necessidades (4) . Outra ideia eficaz nas ações de vigilância é a detecção precoce de câncer do colo do útero (CCU) por meio de programas organizados de rastreamento, que dependem da Atenção Primária à Saúde (APS) na captação das mulheres para a realização do exame citopatológico do colo do útero, e depois, caso haja lesão intraepitelial escamosa de alto grau, encaminhamento para a rede de atenção secundária (5) .…”
Section: Introductionunclassified